(untitled) (Heritage, 2021)
The sectors of the company should, through their organization and business, help the affairs of the overall decision-making process of the top management in the company. Organizational parts of the company that are organized within the sector should, in cooperation with the introduced internal audit of the company, give their practical contribution within the regular business of the company in a way that will contribute to improving the business decision-making of top management in the company. The tasks of internal audit should be closely related to the work of external audit, which performs the tasks of external audit in the company. Internal and external audit should have such an organized structure of work in the audit processes in the company, that they can apply all the adopted standards of the audit profession. This study emphasizes the importance of the practical application of the work of the audit profession in companies in which auditing is performed on the orders of the top management of the company. In addition, auditors should perform their business within the funds approved by top management: in an economical way, i.e. an efficient and effective way during the entire process of performing audit work in the company. The general goal of top management is to provide efficient and quality overall management in the company in such a way that it will provide better and higher quality services. The introduction of external and internal audit in the work of controlling the work of the company, its business, application of adopted procedures, etc., stems precisely from the general goal of top management business. The authors point out that the introduced audit can greatly contribute to the improvement of the overall business results in the company, but this can be achieved only in the case of application of auditor recommendations by the top management of the company.